Gender as a moderator of employee professionalism and performance on customer satisfaction in Indonesian Islamic Banks - Firdayetti, Firdayetti; Damayanti, Sisca; Rahma , Syakila Kania; Chania, Putri Septia (International Journal of Applied Finance and Business Studies, 2025)
The increasingly competitive landscape of Islamic banking in Indonesia urges institutions such as Bank Syariah Indonesia (BSI) to optimize employee performance and professionalism to improve customer satisfaction. However, several customer complaints in West Jakarta raise concerns about service consistency. This study aims to examine the influence of employee performance and professionalism on customer satisfaction, with gender acting as a moderating variable. A quantitative approach was employed using a questionnaire distributed to 120 people BSI customers, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that employee performance significantly affects customer satisfaction (coefficient = 0.297; p = 0.002), and employee professionalism shows a stronger significant effect (coefficient = 0.634; p<0.001). Gender moderates the relationship between professionalism and satisfaction for both male (coefficient = 0.599; p = 0.043) and female customers (coefficient = 0.807; p < 0.001), but its moderating effect on the relationship between performance and satisfaction is only significant for female customers (coefficient = 0.159; p < 0.001), and not for male customers (coefficient = 0.291; p = 0.109). These findings suggest that while gender plays a partial moderating role, the professionalism of employees remains the most critical factor in enhancing customer satisfaction at BSI West Jakarta. Companies should focus on developing employee skills and professionalism while implementing inclusive communication strategies to address potential gender bias. Future research could explore additional moderators or contextual factors to further refine these insights.